2018
DOI: 10.1038/s41379-018-0047-1
|View full text |Cite
|
Sign up to set email alerts
|

Solid papillary carcinoma with reverse polarity of the breast harbors specific morphologic, immunohistochemical and molecular profile in comparison with other benign or malignant papillary lesions of the breast: a comparative study of 9 additional cases

Abstract: Solid papillary carcinoma with reverse polarity is a rare breast cancer of favorable prognosis that can be difficult to diagnose. We report here nine additional cases of this tumor, and we describe its morphologic, immunohistochemical and molecular profile in comparison to other types of papillary and micropapillary lesions of the breast that are intraductal papilloma with usual ductal hyperplasia, encapsulated papillary carcinoma, solid papillary carcinoma and invasive micropapillary carcinoma. We studied nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 45 publications
5
43
0
Order By: Relevance
“…We conducted the immunohistochemical analyses for calretinin and androgen receptor in cases with available material. In agreement with Alsadoun et al (26), the majority (90%; 9/10) of tall cell carcinomas with reverse polarity analyzed showed either diffuse (n=5) of focal (n=4) immunoreactivity for calretinin, and most cases (81%; 9/11) displayed either absent (n=3) or low (<=10%; n=6) androgen receptor expression ( Supplementary Fig. 1A-1D and Supplementary Table 2).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…We conducted the immunohistochemical analyses for calretinin and androgen receptor in cases with available material. In agreement with Alsadoun et al (26), the majority (90%; 9/10) of tall cell carcinomas with reverse polarity analyzed showed either diffuse (n=5) of focal (n=4) immunoreactivity for calretinin, and most cases (81%; 9/11) displayed either absent (n=3) or low (<=10%; n=6) androgen receptor expression ( Supplementary Fig. 1A-1D and Supplementary Table 2).…”
Section: Resultssupporting
confidence: 90%
“…Consistent with prior reports by our group (1,4) and others (10,21,26), we observed a high frequency of IDH2 R172 hotspot mutations in tall cell carcinomas with reverse polarity, which coexisted with PIK3CA mutations in 50% of cases. Whether the tall cell carcinomas with reverse polarity found to lack PIK3CA hotspot mutations analyzed here harbor other genetic alterations affecting genes of the PI3K signaling pathway, such as loss-of-function mutations targeting PI3KR1, as previously reported in PIK3CA-wild type tall cell carcinomas with reverse polarity (1) was not investigated in this study.…”
Section: Discussionsupporting
confidence: 93%
“…Chiang et al performed molecular analysis on 13 cases of TCCRP using whole-exome and targeted sequencing and found that 77% of cases harbored IDH2 mutation at R172 (4). Alsadoun et al, after genetic and transcriptomic profiling of this tumor using whole-exome analysis, showed that the IDH2 gene harbors a hotspot mutation at the level of arginine 172 (R172), which was not present in any other breast carcinoma, in 78% of TCCRP (7). Although IDH2 mutations are commonly identified in many tumors such as secondary gliomas, myeloid malignancy, cholangiocarcinoma, microsatellite stable colorectal cancer, chondrosarcoma etc., they are infrequent among breast tumors but are typically seen in TCCRP (7,(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Alsadoun et al, after genetic and transcriptomic profiling of this tumor using whole-exome analysis, showed that the IDH2 gene harbors a hotspot mutation at the level of arginine 172 (R172), which was not present in any other breast carcinoma, in 78% of TCCRP (7). Although IDH2 mutations are commonly identified in many tumors such as secondary gliomas, myeloid malignancy, cholangiocarcinoma, microsatellite stable colorectal cancer, chondrosarcoma etc., they are infrequent among breast tumors but are typically seen in TCCRP (7,(13)(14)(15)(16)(17). Pareja et al demonstrated that immunohistochemistry using a monoclonal antibody against IDH2 R172S (Clone -11C8B1) is sensitive and specific for TCCRP harboring the IDH2 R172 hotspot mutation (18).…”
Section: Discussionmentioning
confidence: 99%
“…Solid papillary carcinoma with reverse polarity is a rare breast tumour type that has been historically difficult to diagnose. Across two recent exome sequencing studies, IDH2 mutations have been demonstrated to be common, with 17/22 cases harbouring hotspot mutations at R172, one of which was shown to drive oncogenic features and polarity reversal in near‐normal breast cancer cells in vitro . IDH2 encodes isocitrate dehydrogenase, a citric acid cycle enzyme that has also been implicated in the aetiologies of other neoplastic, cardiac and neurological conditions .…”
Section: The Breast Cancer Morphology/classification Spectrummentioning
confidence: 99%